Kenneth M Alexander - Author and Artist - Alexander, Kenneth M (WritingThreeSixty, 2019)
I was born to Dennis and Kathleen Alexander in a single motor garage at 21 Limerick Road in Athlone. In those days, the midwife would do her rounds on a bicycle at the time when the stork was seen flying over the now-collapsed, missing going, gone forever Athlone Towers. Either that or she went to the foot of Table Mountain and placed a hollowed out pumpkin with a precision cut hole in one side. The monkey would come, stick his or her hand in the hole, grab some pips and in trying to pull its hand out in a fist, it gets stuck. The midwife then pounces on the helpless monkey, knocks it out with her case, and then stuffs "it" into that same black case and off she motors on her "dik" wheel bicycle to deliver the latest addition to an Athlone family. The monkey cries with relief when let out of the case. I have since moved on from that belief system. For some reason, the majority of the employers I worked for still believe that. In fact, far too many white people still do. To them we are monkeys and they pay us with peanuts.